Antimicrobial activity of Tea Tree oil (Melaleuca alternifolia) against skin infection causing bacteria and comparison of its effectiveness with that of the Eucalyptus oil, Lemongrass oil and conventional antibiotics. - Mumu, Sinthia Kabir (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.